Fenomena Childfree Ditinjau dari Perspektif Forum Genre Provinsi Jambi - Samudra, Wahyu; Ferdiansyah, Muhammad; Zubaidah, Zubaidah (Universitas Mathla'ul Anwar Banten, 2024)
The childfree phenomenon, which has become a topic of conversation in Indonesia after a YouTuber and influencer revealed his choice, has had its pros and cons. This research aims to understand the childfree phenomenon from the perspective of the Indonesian Genre Forum, Jambi Province. The problem definition includes this forum's views on the factors and impacts of the childfree phenomenon. The decision to be childfree is considered to require mental and physical readiness. There are five factors why someone chooses to be childfree, namely personal, psychological, economic, philosophical and environmental factors. The informants for this research are members of the Jambi Province Genre Forum and genre ambassadors 2023. Using a purposive sampling technique, 8 informants were selected. The research uses descriptive qualitative methods to describe the conditions in the field. The research results concluded that every individual has the right to decide to have children, for varying reasons. The childfree decision has both positive and negative impacts. The research is expected to provide new understanding to readers, including prospective counselors, parents, prospective parents, and the wider community. The implications of the research results include various aspects related to the childfree phenomenon from the perspective of the Jambi Province Genre Forum.